Evaluation of azole-resistant mycobiota and mycotoxins profile in tea - Simões, Ana Beatriz (2021)
Project "Resistant mycobiota and mycotoxigenic profile of tea and medicinal plants” (IPL/2020/TEAResMyc_ESTeSL).